Fuzzy Sets-Based Methods and Techniques for Modern Analytics - Ebrahimnejad, Ali.; Verdegay, José Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book offers a comprehensive, practice-oriented introduction to the field of fuzzy mathematical programming (FMP) as key topic of modern analytics.  FMP plays a fundamental role in dealing with a varied range of problems, such as those concerning smart cities, sustainability, and renewable energies. This book includes an introduction to the basic concepts, together with extensive information on the computational-intelligence-based optimization models and techniques that have been used to date. Special emphasis is given to fuzzy transportation problems. The book is a valuable resource for researchers, data scientists and practitioners dealing with computational-intelligence-based optimization models for analytics.
Fuzzy Set Theory -- Fuzzy Linear Programming -- Linear Programming with Fuzzy Parameters: Simplex Based Approaches -- Linear Programming with Fuzzy Parameters: Non-Simplex Based Approaches -- Fuzzy Transportation Problem.
Keywords: Computational intelligence; Operations research; Artificial intelligence; Management science; Computational Intelligence; Operations Research and Decision Theory; Artificial Intelligence; Operations Research, Management Science